2000
DOI: 10.1046/j.1365-2818.2000.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ion mass spectrometry imaging of the fixation of 15N‐labelled NO in pollen grains

Abstract: We used secondary ion mass spectrometry to image cellular targets of nitrogen oxides (widespread air pollutants) in pollen grains of birch (Betula verrucosa Ehrh.) and cockfoot (Dactylis glomerata L.). The pollen samples were exposed to air supplemented with high doses of 15NO. The pollen grains were then fixed, dehydrated using a newly developed 'vapour phase' preparation method and embedded in LRW resin. Semithin sections were then analysed. Imaging was performed in scanning mode. As usual, the two isotopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The use of CN − is applicable for the nitrogen isotopic analysis using the ratio of 12 C 15 N − / 12 C 14 N − in carbon‐rich materials. (Zinner, Ming, & Ander, 1989; Lhuissier et al, 2000; Aléon et al, 2003; Mostefaoui et al, 2005). For silicate minerals and glasses, NO − is used instead.…”
Section: Simsmentioning
confidence: 99%
“…The use of CN − is applicable for the nitrogen isotopic analysis using the ratio of 12 C 15 N − / 12 C 14 N − in carbon‐rich materials. (Zinner, Ming, & Ander, 1989; Lhuissier et al, 2000; Aléon et al, 2003; Mostefaoui et al, 2005). For silicate minerals and glasses, NO − is used instead.…”
Section: Simsmentioning
confidence: 99%
“…Because it is necessary to measure nitrogen from the secondary ion CN Ϫ , the mass resolution must be sufficient to allow the separation of the mass 27 isobars, 12 C 15 N and 13 C 14 N. Hindie et al [15] have reported in elegant experiments the measure of 12 C 15 N/ 12 C 14 N, 13 C 14 N/ 12 C 14 N, and 13 C 15 N/ 12 C 14 N isotope ratios in cultured cells using a CAMECA IMS 3F. The 12 C 15 N/ 12 C 14 N isotope ratio has also been measured in pollen grains [16]. In both cases, however, the data had to be acquired one mass at a time.…”
mentioning
confidence: 99%
“…In support of this possibility, cell division is important in establishing growth rates (Reshes et al, 2008 ) and in generating diversity in bacteria (Musat et al, 2008 ; Rego et al, 2017 ; Yu et al, 2017 ). The segregation of intracellular material in E. coli is characterized by asymmetry (Lindner et al, 2008 ; Wang et al, 2010 ; Chai et al, 2014 ; Bergmiller et al, 2017 ). Such segregation, followed by cell division, might also generate a coherent metabolic diversity: in the strand-specific model, which has a eukaryotic echo (Klar, 1987 ), the strand-specific hyperstructures that separately accompany each of the parental DNA strands are segregated to separate positions during the replication of the chromosome; this results in one of the daughter cells receiving hyperstructures that steer it toward a slow growth phenotype whilst the other daughter cell receives hyperstructures that steer it toward a fast growth phenotype (Rocha et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%